Experimental and DFT/TD-DFT Studies of [Ru(bbp)2]2+ Complex: FMO Analysis and Global Reactivity Descriptors - Arul Mary, S.; Daniel, Sheeba (Asian Journal of Chemistry, 2026)
The homoleptic ruthenium(II) complex [Ru(bbp)2]2+ (bbp = 2,6-bis(benzimidazol-2-yl)pyridine) has been synthesized and characterized by elemental analysis, UV-Visible, FTIR, 1H NMR, 13C NMR and MALDI-TOF-MS techniques. The spectroscopic data support coordination of the tridentate bbp ligand to the ruthenium center and formation of the proposed complex. Its electronic absorption profile features a characteristic metal-to-ligand charge-transfer (MLCT) transition arising from excitation of metal-centered orbitals to ligand-centered π*-orbitals. DFT calculations at the B3LYP/LANL2DZ level were used to examine the optimized molecular structure, frontier molecular orbitals and electronic properties, while TD-DFT calculations with an acetonitrile solvation model were employed to interpret the observed absorption features. The frontier orbital distribution places the occupied states mainly on the ruthenium center and the low-lying unoccupied states on the coordinated ligands, supporting the MLCT character of the complex. Conceptual DFT descriptors provide insight into its electronic stability, charge-transfer propensity and chemical reactivity. The combined experimental and computational study establishes a coherent relationship between the molecular structure, electronic configuration and optical response of the [Ru(bbp)2]2+ complex.